PD-1, PD-L1, NY-ESO-1, and MAGE-A4 expression in cutaneous angiosarcoma: A case report. Issue 28 (15th July 2022) - Hashimoto, Kazuhiko; Nishimura, Shunji; Shinyashiki, Yu; Ito, Tomohiko; Tanaka, Hiroki; Ohtani, Kazuhiro; Kakinoki, Ryosuke; Akagi, Masao
Abstract : Rationale: The genomic alteration of cutaneous angiosarcoma (cAS) is complex. Treatment efficacy of immunotherapy for cAS remains controversial and prognosis remains poor. Herein, we report a case of cAS with programmed cell death 1, programmed cell death ligand-1, New York esophageal squamous cell carcinoma-1, and melanoma-associated antigen 4. Patient concerns: A 69-year-old man presented with a chief complaint of left thumb pain, with a soft tissue mass in the palmar side of the thumb. He had no past medical history. Three months prior, the man experienced the pain while scuba diving. He visited a nearby clinic, and magnetic resonance imaging revealed a soft tissue tumor on the palmar side of the thumb. He was referred to our hospital and a marginal excisional biopsy was performed. Diagnosis: Pathological findings revealed an angiosarcoma with high-flow serpentine vessels. Interventions: An excision was performed from the base of the thumb to achieve a wide margin. Outcomes: One year after the treatment, the patient has not experienced recurrence, metastasis, or complications. Lessons: Histopathology of the excised specimen was positive for programmed cell death 1, programmed cell death ligand-1, New York esophageal squamous cell carcinoma-1, and melanoma-associated antigen 4; their expression may be a therapeutic target for cAS. Combining immunotherapy with surgical treatment may be effective for cAS.